A Factor Analysis of Students’ Attitudes Towards Statistics in Higher Learning Institution Malaysia - Mansor, Rosnalini; Zaini, Bahtiar Jamili; Md Yusof, Zahayu; Wendy, Wong (Universiti Pendidikan Sultan Idris, 2018)
Attitudes toward statistics have received a great attention by academic and researcher in statistics and mathematics education. This paper investigates students’ attitudes towards statistics in one of the Malaysia higher education institution and determined the factors that explain the attitude of students toward statistics. Stratified sampling method was used to select 274 respondents from 18 classes Elementary Statistics course. The attitudes toward statistics were measured using the Survey Attitude Towards Statistics (SAT-36) scale. Factor analysis was applied to identify the factors on students’ attitude toward statistics. Findings from factor analysis revealed that seven factors that explain the attitude of the students were self-determination, cognitive competence, effort, value of statistics in professional life, difficulty, statistical solving and value of statistics in everyday life. The results suggested that statistics should be demonstrated in more practical way for developing more positive attitude towards statistics. This could further promote the learning process and students’ ability to apply the statistical concepts